Targeting the European Voter : Profiling for Political Advertisement Purposes under the General Data Protection Regulation - Penttilä, Pauliina (My University, 2021)
As people, businesses and commerce increasingly move to the electronic environment, a natural consequence is also the increase in digital advertising. Technological developments make it possible to track individuals in more detail as they move from one device, application or website to another. Personal data can be stored and processed more accurately to monitor and predict the preferences of individuals or target audiences, enabling targeted and well-tailored advertising to be directed at users. Targeted advertising has many advantages, but in the context of political advertising, there are many serious problems in terms of personal data protection, privacy and functioning of democratic societies. The purpose of this dissertation is to research whether targeted advertising may reveal political opinions of natural persons. The EU's General Data Protection Regulation (GDPR) lays down specific conditions for the processing of personal data which reveals the political views of a natural person. Political opinions are, as a concept, open to interpretation, and it is not possible to give a precise definition. Rather, the views which are subject to higher level of protection are to some extent dependent on the context in which they have been revealed. Personal data, which belong to the special categories of data, may be revealed directly and indirectly, even by observing such data that by itself does not meet the criteria for special categories of personal data. Targeting does not appear in EU data protection legislation, but profiling and automatic processing of personal data are regulated in the GDPR. Profiling and automatic processing of personal data are means to generate target audiences used in targeting. Profiling can be utilised to assess the behavior of individuals and to predict their future choices. Profiling can also generate new information about the individuals that are profiled, as well as infer personal data that the individual has not knowingly provided about himself or herself. The output of profiling may also reveal sensitive information about those profiled, such as personal data revealing political opinions of the individuals. Processing of such information is subject to specific requirements of lawful processing due to the serious risks it may pose on the individual.

Ihmisten, yritysten ja kaupankäynnin siirtyessä yhä enenevissä määrin sähköiseen ympäristöön luonnollisena seurauksena on myös digitaalisen mainonnan lisääntyminen. Teknologinen kehitys mahdollistaa yksilöiden yhä yksityiskohtaisemman seuraamisen niin laitteesta, sovelluksesta tai nettisivulta toiseen siirryttäessä. Henkilötietoja kyetään tallentamaan ja käsittelemään entistä tarkemmin yksilöiden tai kohdeyleisöjen mieltymysten tarkkailuun ja ennakoimiseen, mikä mahdollistaa yksilöllisen ja tarkkaan räätälöidyn mainonnan kohdentamisen käyttäjiin. Kohdennetulla mainonnalla on monia etuja, mutta poliittisen mainonnan yhteydessä kohdentamiseen liittyy monia vakavia ongelmia koskien niin henkilötietojen suojaa, yksityisyyttä kuin demokratian toteutumista. Tutkielman tarkoituksena on jäsennellä sitä, liittyykö kohdennettuun mainontaan sellaisten henkilötietojen käsittelyä, josta ilmenee luonnollisen henkilön poliittisia mielipiteitä. EU:n yleinen tietosuoja-asetus (GDPR) asettaa erityisiä ehtoja sellaisten henkilötietojen käsittelylle, joista ilmenee luonnollisen henkilön poliittisia mielipiteitä. Poliittiset mielipiteet ovat käsitteenä avoin tulkinnalle, eikä tarkkarajaista määritelmää ole mahdollista antaa. Erityisiin henkilötietoryhmiin koskevia tietoja voi ilmetä sekä suoraan että välillisesti myös sellaisista tiedoista, jotka eivät itsessään vastaa erityisen henkilötietoryhmän määritelmää. Kohdentaminen tai ”targetointi” ei esiinny EU:n tietosuojalainsäädännössä, mutta sen sijaan profilointia ja automaattista henkilötietojen käsittelyä säännellään tietosuoja-asetuksessa. Profilointi ja automaattinen henkilötietojen käsittely ovat keinoja tuottaa kohdentamisessa käytettyjä kohdeyleisöjä. Profiloinnilla voidaan arvioida yksilöiden käyttäytymistä ja pyrkiä ennakoimaan heidän tulevia valintojaan. Profiloinnilla voidaan myös tuottaa uutta tietoa profiloitavista yksilöistä sekä päätellä sellaisiakin henkilötietoja, joita yksilö ei itse ole tietoisesti antanut itsestään. Profiloinnin lopputuloksena voi myös syntyä erityisten henkilötietoryhmien tietoja kuten sellaisia henkilötietoja, joista ilmenee yksilöiden poliittisia mielipiteitä. Tällaisten tietojen käsittelylle on asetettu erityisiä vaatimuksia niistä yksilölle mahdollisesti aiheutuvien erittäin vakavien riskien vuoksi.
Keywords: EU law, personal data protection, data revealing political opinions, profiling, targeting, EU-oikeus, henkilötietojen suoja, poliittiset mielipiteet, profilointi, kohdentaminen